Plasticity injection material and method for adjusting carbon dioxide emission
The plastic injection material composition, featuring a carbon dioxide absorber, cement, and bentonite, addresses the challenge of maintaining flowability and strength while reducing carbon dioxide emissions by adjusting the blending ratio and replacing cement with a carbon dioxide absorber, resulting in materials with zero or negative carbon dioxide emissions.
Patent Information
- Application Number
- JP2023151694
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
Existing plastic injection materials face challenges in maintaining the same flowability and strength as conventional materials while effectively reducing carbon dioxide emissions, as the use of carbon dioxide absorbers can lead to increased strength and decreased flowability.
A plastic injection material composition that includes a carbon dioxide absorber, cement, and bentonite, with a preferred carbon dioxide absorber being calcium carbonate, and a method to adjust carbon dioxide emissions by adjusting the blending ratio of these components, including replacing part of the cement with a carbon dioxide absorber.
The proposed solution enables the production of plastic injection materials with equivalent flowability and strength to conventional materials while reducing carbon dioxide emissions, as demonstrated by zero or negative carbon dioxide emissions in the examples provided.
Smart Images

Figure 2025044026000001 
Figure 2025044026000002 
Figure 2025044026000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a plastic injection material and a method for adjusting carbon dioxide emissions. [Background technology]
[0002] In recent years, there has been a demand to reduce carbon dioxide emissions in various industries. The construction industry is no exception, and materials that reduce carbon dioxide emissions are being developed. An example of material development is a plastic injection material used to fill gaps behind tunnel linings or cavities in underground structures. Plastic injection materials generally contain a binder such as cement and a plasticizer such as bentonite (see, for example, Patent Document 1). Of these, cement emits large amounts of carbon dioxide during its production, so there is a demand to reduce its use. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-147526 A Summary of the Invention [Problem to be solved by the invention]
[0004] In plastic injection materials, the use of carbon dioxide absorbents instead of cement has been considered in order to reduce the amount of carbon dioxide emissions. However, when carbon dioxide absorbents are used, the strength of the hardened product of the plastic injection material may increase too much, resulting in a decrease in fluidity. On the other hand, if the amount of carbon dioxide absorbent is reduced to increase fluidity, it is difficult to reduce the amount of carbon dioxide emissions. For this reason, it has been difficult to manufacture a plastic injection material that has the same fluidity and hardened product strength as conventional plastic injection materials, while also reducing the amount of carbon dioxide emissions.
[0005] The present invention aims to provide a plastic injection material that reduces carbon dioxide emissions while having fluidity and hardened strength equivalent to conventional plastic injection materials, and a method for adjusting the amount of carbon dioxide emissions during the production of the same. [Means for solving the problem]
[0006] In order to achieve the above object, the present invention provides a plastic injection material containing a carbon dioxide absorbent, cement, and bentonite. In the plastic injection material of the present invention, the carbon dioxide absorbent is preferably calcium carbonate. The plastic injection material of the present invention has a carbon dioxide absorbent content of 150 kg / m 3 ~455kg / m 3 It is preferable that: The carbon dioxide emission control method of the present invention is a method for controlling carbon dioxide emissions by manufacturing a plastic injection material containing a carbon dioxide absorbent, cement, and bentonite by adjusting the mixing ratio of each material contained in the plastic injection material. In the method for adjusting the amount of carbon dioxide emission of the present invention, it is preferable to replace a part of the cement with a carbon dioxide absorbent. Effect of the Invention
[0007] According to the present invention, it is possible to provide a plastic injection material that has fluidity and hardened strength equivalent to conventional plastic injection materials while reducing carbon dioxide emissions, and a method for adjusting the amount of carbon dioxide emissions during the production of the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] (Plastic injection material) The plastic injection material according to the embodiment contains a carbon dioxide absorbent, cement, and bentonite, and further contains other components as necessary.
[0009] <Carbon dioxide absorbent> The carbon dioxide absorbent is included to obtain hardening performance and carbon dioxide absorption performance. The hardening performance is the ability of the carbon dioxide absorbent itself to harden the plastic injection material. The carbon dioxide absorbent having hardening performance can reduce the ratio of cement, which will be described later, in the plastic injection material. Carbon dioxide absorption performance is the ability to fix carbon dioxide in the atmosphere. Carbon dioxide absorbents are manufactured by fixing carbon dioxide. Therefore, by using carbon dioxide absorbents instead of conventional materials, it is possible to reduce the amount of carbon dioxide emissions in plastic injection materials.
[0010] Examples of carbon dioxide absorbents include calcium carbonate, magnesium carbonate, sodium carbonate, sodium hydrogen carbonate, dried sludge obtained by drying dehydrated cake (industrial waste or sludge containing moisture that has been dehydrated), etc. These may be used alone or in combination of two or more.
[0011] The content of the carbon dioxide absorbent is not particularly limited and can be appropriately selected depending on the purpose. 3 ~455kg / m 3 When the content of the carbon dioxide absorbent is within this range, the strength of the hardened product of the plastic injection material can be improved while maintaining the fluidity of the plastic injection material.
[0012] <Cement> The cement is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include various Portland cements such as ordinary, moderate heat, low heat, early strength, ultra early strength, and sulfate resistant cements, blast furnace cement, fly ash cement, and mixed cements such as silica cement, ultra rapid hardening cements such as alumina cement and jet cement, Irwin cement, etc. These may be used alone or in combination of two or more types.
[0013] The cement content is not particularly limited and can be appropriately selected depending on the purpose. 3 More than 300kg / m 3 Less than 50kg / m is preferable. 3 More than 60kg / m 3The following is more preferable. When the cement content is within this range, the strength of the hardened product of the plastic injection material can be improved.
[0014] <Bentonite> Bentonite is a clay mineral whose main component is montmorillonite. Montmorillonite is composed of crystals with a structure in which cations exist between negatively charged layers. Bentonite is broadly classified into sodium type and calcium type depending on the type of cations present between the layers of the montmorillonite crystals. These may be used alone or in combination of two or more types.
[0015] Sodium type bentonite is bentonite that has a large number of sodium ions among the cations present between the layers of montmorillonite. Sodium type bentonite is known to have high swelling properties (high swelling). Calcium bentonite is bentonite that has a large number of calcium ions among the cations present between the layers of montmorillonite. Calcium bentonite is known to have a lower swelling property than sodium bentonite (low swelling property). In addition to sodium-type and calcium-type bentonite, there is also activated bentonite (Na-exchanged bentonite). This is bentonite that has been artificially converted to sodium-type by adding sodium carbonate (Na2CO3) to calcium-type bentonite in order to improve its swelling property, which is its greatest characteristic. Activated bentonite (Na-exchanged bentonite) has a higher swelling property than calcium-type bentonite. Bentonite may be either a synthetic product or a commercially available product.
[0016] The content of bentonite is not particularly limited and can be appropriately selected depending on the purpose. 3 More than 150kg / m 3 When the bentonite content is within this range, the fluidity of the plastic injection material and the strength of the hardened product can be ensured.
[0017] <Other ingredients> The other components are not particularly limited as long as they are those used in conventional plastic injection materials and can be appropriately selected depending on the purpose. Examples of the other components include water, ground granulated blast furnace slag, and expansion agents. The contents of other components are not particularly limited as long as they do not impair the performance of the plastic injection material, and can be appropriately selected depending on the purpose.
[0018] <Manufacturing method of plastic injection material> There are no particular limitations on the method for producing the plastic injection material, and it may be appropriately selected depending on the purpose. For example, there may be mentioned a method in which cement, a carbon dioxide absorbent, and other components are added to a dispersion obtained by dispersing bentonite in water, and the mixture is mixed to obtain the plastic injection material.
[0019] (Carbon dioxide emissions adjustment method) The carbon dioxide emission control method according to the embodiment is a method for controlling carbon dioxide emission by adjusting the mixing ratio of each material contained in the above-mentioned plastic injection material to produce the plastic injection material, and it is preferable to replace a part of the cement with a carbon dioxide absorbing material.
[0020] According to this method for adjusting the amount of carbon dioxide emissions, the plastic injection material is manufactured by adjusting the mixing ratio of each material contained in the plastic injection material, which contains a carbon dioxide absorbent, cement, and bentonite, so that it is possible to adjust the amount of carbon dioxide emissions.
[0021] In addition, by replacing a part of the cement with the carbon dioxide absorbent, a part of the cement, which is a carbon dioxide releasing material, is replaced with the carbon dioxide absorbent, so the mixing ratio of the cement is reduced and the mixing ratio of the carbon dioxide absorbent is increased, thereby making it possible to more efficiently reduce carbon dioxide emissions.
[0022] The amount of carbon dioxide emissions can be evaluated by comparing the amount of carbon dioxide emissions emitted by producing a plastic injection material by adjusting the mixing ratio of a portion of the cement contained in the plastic injection material and the carbon dioxide absorbent, with the amount of carbon dioxide emissions from a normal plastic injection material, i.e., a plastic injection material that does not contain a carbon dioxide absorbent.
[0023] The amount of carbon dioxide emitted from the plastic injection material is calculated by calculating the total amount of carbon dioxide emitted during the production of the plastic injection material, calculating the total amount of carbon dioxide absorbed, and then calculating the total amount of carbon dioxide emitted and the total amount of carbon dioxide absorbed for the plastic injection material.
[0024] Total carbon dioxide emissions are the sum of the carbon dioxide emissions of carbon dioxide-emitting materials (cement, ground granulated blast furnace slag, and bentonite). In other words, it is the sum of the carbon dioxide emissions of each material, calculated by multiplying the amount of each material used per unit amount (1 ton) in the plastic injection material by the amount of carbon dioxide emissions per unit amount (1 ton) based on inventory data. EXAMPLES
[0025] Examples of the disclosed technology will be described below, but the disclosed technology is in no way limited to these examples.
[0026] (Examples 1 to 6, Comparative Examples 1 to 2) Details and symbols of the materials used in the examples are shown in Table 1.
[0027] [Table 1]
[0028] The carbon dioxide absorbent used was calcium carbonate produced by blowing exhaust gas, the main component of which was carbon dioxide, onto sludge water.
[0029] A plastic injection material (hereinafter sometimes referred to as "sample") was prepared with the composition shown in Table 2. Specifically, water was first poured into a container, and bentonite (V) was added to the water over 30 seconds, and mixed for 2 minutes with a hand mixer. Next, the binder (BB, NC, BS), carbon dioxide absorbent (E), and optionally, the expansion agent (EX) were added to the container containing the bentonite over 30 seconds, and mixed for 1 minute to obtain a plastic injection material. The carbon dioxide emission of the obtained plastic injection material was calculated, and the flow, compressive strength, and shrinkage rate were measured. The calculation results and measurement results are shown in Table 4.
[0030] [Table 2]
[0031] <Carbon dioxide emissions> The amount of carbon dioxide emitted or fixed (i.e., amount of carbon dioxide absorbed) of the materials used in the examples is shown in Table 3. The values for each material were based on the following values.
[0032] [Table 3]
[0033] The values in Table 3 are as shown below. *1: Japan Society of Civil Engineers, Concrete Technology Series, "Environmental Impact of Concrete", PI-87, Table 4.2.1 *2: Ministry of the Environment website: Emissions unit database for calculating greenhouse gas emissions of organizations throughout the supply chain, "Other ceramic and stone products" *3: Assumed value by manufacturer
[0034] As for the specific calculation method, for example, the calculation for Example 2 was performed as follows. Carbon dioxide emissions = Content of B-type blast-furnace slag cement × Carbon dioxide emissions of B-type blast-furnace slag cement + Content of bentonite × Carbon dioxide emissions of bentonite - Content of carbon dioxide absorbent × Amount of carbon dioxide fixed by carbon dioxide absorbent =250(kg / m 3 )×458.7(kg-CO2 / t) / 1,000+110(kg / m 3 )×112(kg-CO2 / t) / 1,000-455(kg / m 3 )×390.0(kg-CO2 / t) / 1,000 =-50.455(kg / m 3 ) Moreover, for Example 5, the calculation was performed as follows. Carbon dioxide emissions = Ordinary Portland cement content x Carbon dioxide emissions of ordinary Portland cement + Content of ground granulated blast furnace slag x Carbon dioxide emissions of ground granulated blast furnace slag + Content of bentonite x Carbon dioxide emissions of bentonite - Content of carbon dioxide absorbent x Amount of carbon dioxide fixed by carbon dioxide absorbent =50(kg / m 3 )×757.9(kg-CO2 / t) / 1,000+150(kg / m 3 )×24.1(kg-CO2 / t) / 1,000+125(kg / m 3 )×112(kg-CO2 / t) / 1,000-400(kg / m 3 )×390.0(kg-CO2 / t) / 1,000 =-100.490(kg / m 3 )
[0035] <Flow> The flow test was conducted based on the method described in JHS313 (Test method for air mortar and air mold) of "NEXCO Test Methods, Part 3, Concrete-related Test Methods." Specifically, a cylinder of 80mm diameter x 80mm height filled with a sample was pulled up, and the average value was measured for the spread of the bottom of the sample in two directions. To be used as a plastic injection material, it is necessary for the spread to be within the range of 80mm to 155mm. The measurement results are shown in Table 4.
[0036] <Compressive strength> The compressive strength was measured based on JIS A 1216 (uniaxial compression test for soil). The test material was 28 days old. For use as a plastic injection material, the compressive strength must be 1.5 N / mm 2(3N / mm for plastic injection material without adding expansion agent) 2 The measurement results are shown in Table 4.
[0037] <Shrinkage rate> Each plastic injection material was packed into a Summit can with an inner diameter of 100 mm and a height of 200 mm, sealed and cured, and the amount of settlement was measured after 28 days. When used as a plastic injection material, it is necessary that the settlement be 2% or less. The measurement results are shown in Table 4.
[0038] [Table 4]
[0039] From the results in Table 4, the plastic injection materials of Examples 1 to 6 had zero or negative carbon dioxide emissions, whereas the plastic injection materials of Comparative Examples 1 and 2 had positive carbon dioxide emissions. This makes it clear that the plastic injection material of this embodiment has a reduced carbon dioxide emission compared to conventional plastic injection materials (Comparative Examples 1 and 2). In addition, the flow, compressive strength, and shrinkage rate measurement results of the plastic injection materials of Examples 1 to 6 were almost the same as those of conventional plastic injection materials (Comparative Examples 1 and 2). Therefore, it was revealed that the fluidity (flow) and hardened strength (compressive strength) of the plastic injection material according to this embodiment are equivalent to those of conventional plastic injection materials. The cement content of the plastic injection materials in Examples 1 to 3 was 250 kg / m 3 The carbon dioxide absorbent content is 330 kg / m 3 ~455kg / m 3 In contrast, the cement content of the plastic injection material in Comparative Example 1 is 250 kg / m 3 and no carbon dioxide absorbent is included. That is, the plastic injection materials of Examples 1 to 3 are plastic injection materials in which part of the cement, which is a carbon dioxide releasing material, is replaced with a carbon dioxide absorbing material. Similarly, the content of cement and ground granulated blast furnace slag (carbon dioxide releasing material) in the plastic injection materials of Examples 4 to 6 is 200 kg / m 3The carbon dioxide absorbent content is 150 kg / m 3 ~405kg / m 3 In contrast, the content of cement and ground granulated blast furnace slag in the plastic injection material of Comparative Example 1 was 240 kg / m 3 In other words, the plastic injection materials of Examples 4 to 6 are plastic injection materials in which part of the cement, which is a carbon dioxide releasing material, is replaced with a carbon dioxide absorbing material. From the above, it has become clear that the plastic injection material of the present embodiment is a plastic injection material that has fluidity and hardened strength equivalent to conventional plastic injection materials while reducing carbon dioxide emissions.
Claims
1. A plastic injection material comprising a carbon dioxide absorbent, cement, and bentonite.
2. 2. The plastic injection material according to claim 1, wherein the carbon dioxide absorbent is calcium carbonate.
3. The carbon dioxide absorbent content is 150 kg / m 3 ~455kg / m 3 The plastic injection material according to claim 1 or 2,
4. A method for adjusting carbon dioxide emissions, comprising the steps of: manufacturing a plastic injection material containing a carbon dioxide absorbent, cement, and bentonite by adjusting the mixing ratio of each material contained in the plastic injection material, thereby adjusting the amount of carbon dioxide emissions.
5. The method for adjusting carbon dioxide emission according to claim 4, wherein a part of the cement is replaced with the carbon dioxide absorbent.
Citation Information
Patent Citations
Super-quick hardening plastic grout material, and injection method of super-quick hardening plastic grout material
JP2021147526A